2021
DOI: 10.3390/app112110062
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Machine Learning Algorithms in Automatic Identification and Extraction of Water Boundaries

Abstract: Monitoring open water bodies accurately is important for assessing the role of ecosystem services in the context of human survival and climate change. There are many methods available for water body extraction based on remote sensing images, such as the normalized difference water index (NDWI), modified NDWI (MNDWI), and machine learning algorithms. Based on Landsat-8 remote sensing images, this study focuses on the effects of six machine learning algorithms and three threshold methods used to extract water bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…Large-scale riverbank monitoring requires intensive resources and continuity, which is vital for the Mekong River Basin, where several developments on the main river and its tributaries significantly affect sedimentation. In recent years, machine learning algorithms have helped to improve the accuracy of water body detection; however, they are still in the developmental stage [50]. Hence, the water index method is more suitable for detecting large-scale riverbanks along the Mekong River and assessing changes in the river body over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large-scale riverbank monitoring requires intensive resources and continuity, which is vital for the Mekong River Basin, where several developments on the main river and its tributaries significantly affect sedimentation. In recent years, machine learning algorithms have helped to improve the accuracy of water body detection; however, they are still in the developmental stage [50]. Hence, the water index method is more suitable for detecting large-scale riverbanks along the Mekong River and assessing changes in the river body over time.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning methods were found to outperform the water index-based method in specific areas and terrains [42][43][44][45][46]. However, when water detection was performed in the same location at different image acquisition times using the same machine learning algorithm, accuracy was significantly reduced [50], requiring the model to be retrained, which was resource intensive. Machine learning algorithms help to improve accuracy; however, they are still in the developmental stage [50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictive models are selected by comparing and analyzing various regression algorithms from the literature. From the profound literature that discussed on the rationale behind the selection of regression algorithms, it was reported that the performance of predictive models depends on the methodologies implemented, the dataset created 50 , 64 69 , the size and heterogeneity of the dataset 70 . Regression algorithms differ in their principles of operation, advantages, and limitations.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning-based water body segmentation algorithms build a relationship between water body samples and masks, which reduces the reliance on segmentation thresholds. Many popular algorithms such as Support Vector Machine (SVM) [9], Random Forests (RF) [10], Decision Tree (DT), and Deep Learning (DL) have been developed in remote sensing image segmentation [11,12]. DL has attracted more attention in image segmentation mainly due to its strong ability to extract variables to express feature information [13], which boosts the intelligent and automatic interpretation of remote sensing images.…”
Section: Introductionmentioning
confidence: 99%